Konflik Minoritas di Timur Tengah: Studi Kasus Konflik Etnis Kurdi - Assri, Bahy Chemy Ayatuddin (UI Scholars Hub, 2021)
This paper attempts to explain the roots of the Irak and Syria Kurdish ethnic conflict by using the analysis of the Broken Windows theory. The theory that was conceived by a criminologist named George L. Kelling and Cathrine M. Coles is trying to explain something small, if not addressed, it will cause something big. An epidemic will spread depending on the community and the environment. Just like what happened with the Kurds in the Middle East. This group received unfair treatment by the local regime, so the epidemic of freedom and having its own territory spread. A wave of resistance continues to be launched, ranging from the small to the large. Finally, something small can become a big issue, for example Kurdish forces in Iraq and Syria have trained troops and they use the chaotic environment to conduct a referendum on autonomous regions. It means something small (the Kurdish Ethnic resistance movement) that is not given much attention, then presents something big (like Kurdish forces in Iraq and Syria supported by the US to hold a referendum). Keywords: Kurdish Ethnic, Broken Windows Theory, Epidemic, Wave of Resistance Tulisan ini berusaha memaparkan tentang akar konflik Etnis Kurdi Irak dan Suriah dengan menggunakan analisis teori Broken Windows. Teori yang digagas oleh kriminolog bernama George L. Kelling dan Cathrine M. Coles ini berusaha memaparkan sesuatu yang kecil, apabila tidak diperhatikan maka akan menimbulkan sesuatu yang besar. Sebuah epidemi akan menyebar tergantung kepada masyarakat dan lingkungan. Sama seperti apa yang terjadi dengan Etnis Kurdi di Timur Tengah. Kelompok ini mendapatkan perlakuan yang tidak adil oleh rezim setempat, sehingga epidemi akan kebebasan dan memiliki wilayah sendiri tersebar. Gelombang perlawanan terus dilancarkan, mulai dari yang kecil sampai yang besar. Akhirnya sesuatu yang kecil bisa menjadi perkara besar, contohnya pasukan Kurdi di Irak dan Suriah memiliki pasukan yang sudah terlatih dan mereka memanfaatkan keadaan sekitar yang sedang kacau untuk melakukan referendum wilayah otonom. Artinya sesuatu yang kecil (gerakan perlawanan Etnis Kurdi) yang tidak terlalu diperhatikan, kemudian menghadirkan sesuatu yang besar (seperti pasukan Kurdi di Irak dan Suriah yang didukung oleh AS untuk melaksanakan referendum). Kata Kunci: Etnis Kurdi, Teori Broken Windows, Epidemi, Gelombang Perlawanan